Pengaruh Tren Fashion ‘On Shopee vs On Me’ di TikTok terhadap Impulsive Buying Generasi Z - Fanny Dwi Anggreany; Sisca Aulia (Prologia, 2026)
The rapid expansion of social media, which has become a significant platform for many aspects of human existence, including socializing and purchasing items online. TikTok is a popular and frequently utilized communication medium. TikTok has also evolved into a platform for exchanging brief, entertaining material, such as product recommendations or trends. The purpose of this study is think about is to see at how the 'On Shopee vs On Me' trend on TikTok affects Generation Z's impulsive buying. The primary theoretical concepts used in this study are fashion trends and impulsive buying. This study takes a quantitative strategy, collecting information through a survey. This study's demographic and sample comprise TikTok Generation Z users who may have been exposed to the trend content 'On Shopee vs On Me,' with a add up to test measure of 96 respondents. Research findings, with a coefficient of determination test of 20.5%, appear that there's a positive and considerable affiliation among the trend ‘On Shopee vs On Me’ and Generation Z's impulsive buying behavior, while the remaining results are influenced by other factors. These findings demonstrate TikTok's effectiveness as a marketing medium for persuading the younger generation to become more consumerist. Pesatnya pertumbuhan media sosial yang menjadi platform penting untuk berbagai aspek kehidupan manusia, seperti untuk berinteraksi hingga membeli barang secara online. TikTok menjadi platform yang popular saat ini dan banyak digunakan untuk berkomunikasi. TikTok juga menjadi media untuk berbagi konten singkat dan menarik, seperti rekomendasi produk atau tren. Tujuan dari studi ini adalah untuk menganalisis dampak tren fashion‘On Shopee vs On Me’ di TikTok terhadap impulsive buying generasi Z. Konsep teori yang paling penting dalam penelitian ini adalah tren fashion dan impulsive buying. Penelitian ini menggunakan pendekatan kuantitatif melalui pengumpulan data kuesioner. Total sampel 96 responden yakni kuesioner disebarkan kepada generasi Z yang menggunakan TikTok dan berpotensial terpapar konten tren ‘On Shopee vs On Me’ dengan total sampel 96 responden Hasil penelitian didasarkan pada uji koefisien determinasi sebesar 20,5%. Hal ini menunjukkan adanya korelasi positif dan pengaruh yang signifikan antara tren ‘On Shopee vs On Me’ terhadap impulsive buying generasi Z, sementara sisa hasil uji dipengaruhi oleh faktor lainnya. Hasil ini menunjukkan adanya dampak TikTok sebagai platform pemasaran yang mampu mendorong generasi muda untuk menjadi konsumtif.